Unmaking Boundaries: Gender and the Nigerian Literary Imagination - Anigala, Ogochuku O.; Eguvwebere, Adanma Anthonia (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
Unmaking Boundaries: Gender and the Nigerian Literary Imagination is a publication that examines how Tomi Adeyemi's novel Children of Virtue and Vengeance , a fantasy action-adventure novel, un-makes, enumerates, and reconfigures patriarchal narratives as dictated by Western social norms. Adeyemi, who writes with expressive, poetic language, challenges and redefines traditional roles attributed to male rulers. The research posits that decolonial feminist methods anchored in Oyèrónkẹ́ Oyěwùmí’s pivotal work and the historical suppression of indigenous epistemologies have been instrumental in reimagining African literature. Through intensive qualitative analysis, the paper identifies complex female leadership roles such as Zélie and Amari, whose paths cross traditional boundaries and offer different visions of power and agency in Nigerian literature. It also notes that aspects of masculinity are touched upon. Characters like Inan and Roën elucidate inconsistencies associated with the conventional patriarchal era and the possibilities of fluid reimagining. With comparative analyses of classical and contemporary works written in Nigeria, the article places Adeyemi's novel within the larger literature discourse about reclaiming indigenous mythologies and exploring colonial roots. Keywords: Unmaking, Boundaries, Decolonial Feminism, Indigenous Epistemologies.